Assessment of iron nanoparticle distribution in mouse models using ultrashort‐echo‐time MRI. (1st February 2022) - Boss, Andreas; Heeb, Laura; Vats, Divya; Starsich, Fabian H. L.; Balfourier, Alice; Herrmann, Inge K.; Gupta, Anurag
Abstract : Microscopic magnetic field inhomogeneities caused by iron deposition or tissue‐air interfaces may result in rapid decay of transverse magnetization in MRI. The aim of this study is to detect and quantify the distribution of iron‐based nanoparticles in mouse models by applying ultrashort‐echo‐time (UTE) sequences in tissues exhibiting extremely fast transverse relaxation. In 24 C57BL/6 mice (two controls), suspensions containing either non‐oxidic Fe or AuFeO x nanoparticles were injected into the tail vein at two doses (200 μg and 600 μg per mouse). Mice underwent MRI using a UTE sequence at 4.7 T field strength with five different echo times between 100 μs and 5000 μs. Transverse relaxation times T 2 * were computed for the lung, liver, and spleen by mono‐exponential fitting. In UTE imaging, the MRI signal could reliably be detected even in liver parenchyma exhibiting the highest deposition of nanoparticles. In animals treated with Fe nanoparticles (600 μg per mouse), the relaxation time substantially decreased in the liver (3418 ± 1534 μs (control) versus 228 ± 67 μs), the spleen (2170 ± 728 μs versus 299 ± 97 μs), and the lungs (663 ± 101 μs versus 413 ± 99 μs). The change in transverse relaxation was dependent on the number and composition of the nanoparticles. By pixel‐wise curve fitting, T 2 * maps were calculated showing nanoparticle distribution. In conclusion, UTE sequences may be used to assess and quantify nanoparticle distribution in tissues exhibiting ultrafast signal decay in MRI. Abstract : Microscopic magnetic field inhomogeneities caused by iron deposition or tissue‐air interfaces may result in rapid decay of transverse magnetization in MRI. UTE sequences may be used to detect and quantify the distribution of iron‐based nanoparticles in mouse models in tissues exhibiting extremely fast transverse relaxation.